2017
DOI: 10.3389/fimmu.2017.00544
|View full text |Cite
|
Sign up to set email alerts
|

Why the Immune System Should Be Concerned by Nanomaterials?

Abstract: Particles possess huge specific surface area and therefore nanomaterials exhibit unique characteristics, such as special physical properties and chemical hyper-reactivity, which make them particularly attractive but also raise numerous questions concerning their safety. Interactions of nanomaterials with the immune system can potentially lead to immunosuppression, hypersensitivity (allergy), immunogenicity and autoimmunity, involving both innate and adaptive immune responses. Inherent physical and chemical NP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 63 publications
1
70
0
3
Order By: Relevance
“…Gallo and Gallucci, 2013, first alluded to the idea of NP‐associated molecular patterns (NAMPs) as studies demonstrated that NPs could be recognized by immune cells, a concept that continues to be supported by a growing body of evidence . As previously mentioned in this review, NPs have been shown to directly bind SRs on macrophages, both class A and class B, inducing phagocytosis and/or NLRP3 inflammasome activation.…”
Section: Nps As Molecular Patternsmentioning
confidence: 95%
See 2 more Smart Citations
“…Gallo and Gallucci, 2013, first alluded to the idea of NP‐associated molecular patterns (NAMPs) as studies demonstrated that NPs could be recognized by immune cells, a concept that continues to be supported by a growing body of evidence . As previously mentioned in this review, NPs have been shown to directly bind SRs on macrophages, both class A and class B, inducing phagocytosis and/or NLRP3 inflammasome activation.…”
Section: Nps As Molecular Patternsmentioning
confidence: 95%
“…The variability of entry route is thought to be dependent on the particles’ physicochemical characteristics, such as size and agglomeration state . Various particle coatings can also influence mechanism of NP uptake, and can be both intentionally applied prior to administration or acquired as a biocorona through molecular interactions with various proteins, carbohydrates, and lipids within the body . SiO 2 NPs coated with different functional groups, for example, were all endocytosed to varying degrees following the binding of SRs …”
Section: Nps and The Intestinal Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…The "danger signals" would act on DCs, in aseptic conditions, in a similar manner to the microbial molecular patterns. Therefore, the question to be addressed is whether engineered NP could act as danger signals, as previously suggested for ultrafine or diesel exhaust particles [14] and could be considered as NAMPs (nanoparticle-associated molecular patterns) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these factors, the exposure route, surface chemistry and steric effects of their coating impact biodistribution, and determine the level of GNPs' toxicity [20][21][22][23][24]. When used as nanomedicine, GNPs' immunomodulatory properties are often associated with GNPs' uptake by antigen-presenting cells (e.g., macrophages, dendritic cells) and neutrophils, altering their function and T-cell polarisation capacity [25]; therefore, the study of GNPs' interactions with immune cells is undoubtedly of crucial interest.…”
Section: Introductionmentioning
confidence: 99%